The impacts of formal and informal institutions on a forest management project in Cameroon - Ashu, Samuel Tabi Nkongho (2016)
The thesis explores how the implementation of a new forest law in Cameroon affects and interacts with the traditional authority system that previously regulated the forest use and forest management. The concepts of “Institutional Interplay”, “Cross scale institutional linkages” and “Institutional design (Ostrom 2005)” were used to analyse how interactions of local institutions and stakeholders influence community based forest management (CBFM) process in Bimbia Bonadikombo (BB) community. The Institutional Analysis and Development (IAD) framework provided a descriptive and evaluation tool that examined formal and informal (rules) process and interaction in BB. The method of data collection was through interviews (mostly open ended), and focus group discussion. The research made use of primary and secondary sources of data. Participatory tools included transect walk with a target group and participant observation. Some key informants were interviewed and phone interviews were also used to obtain information. Data collected was analysed both quantitatively and qualitatively. Institutional and stakeholder analysis was done using a Venn diagram. In this thesis, I argue that the interactions redefine forest governance and suggest risks of recentralization. Powerful actors especially the government, Limbe III municipality, donor organisations have influenced the CBFM process, and have jointly marginalized the voices of local farmer groups and other users. The implementation process of the law 94/01 takes precedence over customary tenure, which justifies the conflict between native and non-native farmers in Bimbia Community, and why a user group approach as an interplay management strategy is adopted at the operational level of decision-making for the farmers. To say that the implementation process of law 94/01 is very interactive and supportive of CBFM practice is simplistic and misses the point. The participatory forest management system could be described as a” contractual partnership” between the state and the village communities. The study reveals that farmers in BB, prefer to deal with institutions that have existed and successfully support community forest initiatives that offer control overland by local communities as part of a trade off in their interaction.